Finding the evidence: Screening of Military Family Research, 2014–2017. Issue 10 (October 2019) - Yablonsky, Abigail Marter; Brock, Whitney W.; Whalen, Allyson E.; Melvin, Kristal C.; Agazio, Janice
Abstract : Abstract: Of 1.3 million active duty service members, the majority have family responsibilities; 54.3% are married, and 41.2% have at least one child. The authors sought to determine existing areas of focus in military family research and to identify areas that are currently understudied. The authors queried four literature databases from January 2014 to May 2017, and 2, 502 articles were identified in the initial catchment. All 595 article abstracts that met inclusion criteria were sorted into one or more of 12 topics. Topics with the highest number of articles included Mental Health and Care ( n = 276), Adult/Couple Partner Relationships ( n = 247), and Deployment Issues ( n = 244). Topics with sparse articles included Maternal/Child & Newborn Health ( n = 27), Health Promotion ( n = 10), and Special Heath Care Needs ( n = 4). The three topics with the highest number of articles reflect interdependent and overlapping themes and showcase the importance of family relationships to the operational readiness of active duty members. The topics with fewer numbers of articles highlight areas where more evidence is needed. Understanding the current evidence allows nurse practitioners to support military families appropriately in real time.